1983
DOI: 10.1002/1097-0142(19830915)52:6<1093::aid-cncr2820520627>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of pneumonitis in immunocompromised patients by open lung biopsy

Abstract: The records of 59 immunocompromised patients with fever and pulmonary infiltrates who underwent open lung biopsy, were reviewed. A specific diagnosis was made by lung biopsy in 49 (83%) patients, and in 32 instances (54%) the diagnosis was a treatable infection. Only two (3.4%) false‐negative biopsies occurred. Transplant recipients were more likely to have a specific, treatable pneumonia (74%) than patients with a reticuloendothelial malignancy (42%, P < 0.05). This was due to a greater frequency of bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…Open lung biopsy may identify only a nonspecific pathologic pattern of acute diffuse lung injury, interstitial fibrosis, or chronic pneumonia and not clarify the precipitating cause of the pulmonary process resulting in no change in therapy. Further, even if a specific diagnosis is found, some studies of open lung biopsies in immunocompromised patients have been unable to document that this leads to prolonged survival (5,8,(11)(12)(13). Finally, the results of prior studies on the yield of open lung biopsy may have only limited applicability to current patients because of the changing spectrum and frequency of pulmonary complications in immunocompromised hosts.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Open lung biopsy may identify only a nonspecific pathologic pattern of acute diffuse lung injury, interstitial fibrosis, or chronic pneumonia and not clarify the precipitating cause of the pulmonary process resulting in no change in therapy. Further, even if a specific diagnosis is found, some studies of open lung biopsies in immunocompromised patients have been unable to document that this leads to prolonged survival (5,8,(11)(12)(13). Finally, the results of prior studies on the yield of open lung biopsy may have only limited applicability to current patients because of the changing spectrum and frequency of pulmonary complications in immunocompromised hosts.…”
mentioning
confidence: 68%
“…Although these numbers are small, the low yield and high overall mortality has made us very wary about sending such patients to open lung biopsies. Others have also reported that neutropenic patients have a high likelihood of having nonspecific pathologic findings (6,11). Our study is not able to determine if those biopsied while on a ventilator might have had a better outcome with a biopsy if the procedure had been done earlier in their course.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the findings of SLB in immunocompromised patients showed that a specific diagnosis was obtained in 32-82% of patients [13,[20][21][22][23][24] and that the procedure led to a change in therapy in 28-69% [7,9,21,23]. A recent study by White et al of 67 immunocompromised patients with hematological malignancy including 25 post-HSCT patients found a specific diagnosis in 62% of cases, and overall changes in therapy based on the biopsy results were made in 57% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumothorax, hydropneumothorax, hemothorax, empyema, subcutaneous emphysema, wound hematoma, surgical site infection, bronchopleural fistula, and bacterial pneumonia are consistently reported. 21,102,107,[111][112][113][114] The most serious complications that can add considerable morbidity and mortality are empyema, bronchopleural fistula, and bleeding requiring reoperation. Table 1 shows the rates of these complications according to different authors.…”
Section: Tbb and Olbmentioning
confidence: 99%